Efektivitas Program Pemberian Makanan Tambahan (PMT) Bagi Balita Gizi Kurang di Puskesmas Karangtengah Kota Sukabumi - Richan Rifalzah; Yana Fajar FY. Basori; Andi Mulyadi (Jayapangus Press, 2026)
This study aims to analyze the effectiveness of the Supplementary Feeding Program (PMT) for undernourished toddlers at the Karangtengah Public Health Center, Sukabumi City, for the 2025–2026 period. Utilizing a descriptive-inductive qualitative method combined with the effectiveness theory of Mutiarin and Zaenudin (2014), data were gathered through in-depth interviews with four key informants, field observations, and documentation. The results demonstrate a duality in program effectiveness. Operationally, the program was effective, as evidenced by smooth door-to-door distribution, high parental satisfaction, and a physical recovery rate of approximately 80% among the reached toddlers, measured by anthropometric indicators of weight gain and improved nutritional status. However, in terms of macro-effectiveness, the program was not fully optimal due to limited program coverage, which stagnated at 36.78% by the end of 2025 due to delayed budget realization, alongside clinical barriers such as comorbidities (Tuberculosis and congenital heart disease) in toddlers. The study concludes that while the program succeeded in distribution execution and direct recovery of the reached targets, it requires broader program coverage and integrated medical intervention in the upcoming period to achieve comprehensive macro-effectiveness.